Umea. - Hoet, Jan (Umea : Konsthögskolan - Umea Universitet, 1998)
Lindgren, Anders ; Carnemalm, Björn ; Laukkanen, Helena ; Aaro, Cecilia ; Sandstig, Maria ; Renström, Anna ; Hedborg, Clara ; Nobel, Jonas ; Wahlberg, L.E. ; Aberg, Mikael ; Svensson, Ingela ; Degerman, Markus
Kära Examensklass - 98, Konsthögskolan - Umea Universitet, Umea, 1998
Engels & Zweeds
kunstcatalogus